2010
DOI: 10.4141/cjas09089
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of wheat or corn dried distillers’ grains with solubles on performance and carcass characteristics of feedlot steers

Abstract: . 2010. Evaluation of wheat or corn dried distillers' grains with solubles on performance and carcass characteristics of feedlot steers. Can. J. Anim. Sci. 90: 259Á269. A study was conducted on crossbred steers (n0275; 376924 kg) to evaluate performance and carcass quality of cattle fed wheat or corn dried distillers' grains with solubles (DDGS). The control ration contained 86.6% rolled barley grain, 5.7% supplement and 7.7% barley silage (DM basis). The four treatments included replacement of barley grain at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
43
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 29 publications
14
43
3
Order By: Relevance
“…Moreover, Gibb et al (2008) have reported that ADG was similar among feedlot cattle that were fed finishing diets containing DDGS at 200, 400 or 600 g/kg DM DDGS replacing barley grain. In contrast to our results, several studies have reported improvements in ADG and feed efficiency in beef cattle fed DDGS (McKinnon and Walker 2008;Black 2009;Walter et al 2010). Felix et al (2012) observed that ADG was improved when feedlot lambs were fed DDGS at 200 g/kg; whereas no significant differences were observed when included at 0, 400, or 600 g/kg DM.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, Gibb et al (2008) have reported that ADG was similar among feedlot cattle that were fed finishing diets containing DDGS at 200, 400 or 600 g/kg DM DDGS replacing barley grain. In contrast to our results, several studies have reported improvements in ADG and feed efficiency in beef cattle fed DDGS (McKinnon and Walker 2008;Black 2009;Walter et al 2010). Felix et al (2012) observed that ADG was improved when feedlot lambs were fed DDGS at 200 g/kg; whereas no significant differences were observed when included at 0, 400, or 600 g/kg DM.…”
Section: Discussioncontrasting
confidence: 99%
“…This contradicts our observations from the present study, if we assume that the FA composition of omasal digesta is reflective of that of ruminal digesta. In the study of Aldai et al (2012), C18:2n-6 intakes [calculated from dietary C18:2n-6 contents and DM intakes that were reported by Walter et al (2010), companion paper to Aldai et al (2012)] of cows fed W-DDGS ranged from 159 to 205 g d (1 , whereas C18:2n-6 intakes in cows fed W-DDGS in the current study ranged from 335 to 466 g d (1 . A possible explanation for these discrepant results could, therefore, relate to these differences in C18:2n-6 intakes as more substrate was available for ruminal BH in the current study when compared with that of Aldai et al (2012).…”
Section: Milk Fatty Acid Compositionmentioning
confidence: 89%
“…In barley grain-based inishing diets, no protein supplement is necessary since the protein requirement is met (12%). Feed consumption was either linearly increased [14,25], linearly decreased [26] or did not difer [13] with increasing the inclusion rate of wheat distiller grain from 10, 20, 40 to 60%; however, growth performance and feed eiciency were overall not afected with increasing the replacement of grain with wheat distiller grain. These results indicated that wheat distiller grain can be successfully incorporated to substitute a portion of grain within inishing diets with minimal or no adverse impact on catle growth performance.…”
Section: Distiller Grain For Inishing Catlementioning
confidence: 97%
“…These results suggest that replacement of barley silage with wheat distiller grain cause favourable changes in the faty acid proile of meat such as omega-3 faty acids in beef. Similarly, Walter et al [25] included 40% wheat distiller grain in inishing diets and observed no adverse impact on carcass quality or sub-primal boneless boxed beef yields. Animals fed wheat distiller grain included at 20 or 40% produced backfat, yield, ribeye area and marbling scores consistent with barley-inished catle with no change in meat quality (chemical composition, cooking time, cooking loss, tenderness, drip loss, colour) or diferences in sensory tests (taste, smell, sight) [29].…”
Section: Distiller Grain For Inishing Catlementioning
confidence: 99%